Morphological and molecular analyses support the amphi-Atlantic distribution and taxonomic status of the snapping shrimp Alpheus intrinsecus Spence Bate, 1888 (Crustacea: Decapoda: Alpheidae) - Cunha, Andressa Maria; Terossi, Mariana; Mantelatto, Fernando L.; Almeida, Alexandre O. (Zootaxa, 2017)
The objective of this study was to review the amphi-Atlantic snapping shrimp Alpheus intrinsecus Spence Bate, 1888 combining traditional taxonomy and molecular analysis, in order to confirm the distribution pattern reported for the species, and to verify the existence of cryptic species among specimens of both sides of the Atlantic. In total, 134 specimens previously identified as A. intrinsecus from the western Atlantic (Mexico, Veracruz; Venezuela, Sucre; Suriname; Brazil, Pernambuco, Bahia, Rio de Janeiro, São Paulo, and Santa Catarina) and eastern Atlantic (Sierra Leone, Ghana, Benin, Cameroon, Democratic Republic of Congo, Angola) were examined. Main diagnostic characters were analyzed. Although unusual for the group, the mouthparts were also examined to provide additional comparative data. The species redescription and illustrations were carried out based on specimens from the coast of Bahia (Brazil), near the type locality. Furthermore, all existing information on the species was compiled. Morphological analysis indicated the absence of consistent differences between specimens from the various locations, and genetic analyses using the mitochondrial gene 16S corroborated these results. Therefore, the amphi-Atlantic distribution of A. intrinsecus was confirmed, and the hypothesis of existence of two or more cryptic species was refuted. The southern limit of distribution in the eastern Atlantic was extended to Angola.